2012
DOI: 10.52283/nswrca.ajbmr.20120206a04
|View full text |Cite
|
Sign up to set email alerts
|

SELF-CONTROL AS A MODERATOR OF THE RELATIONSHIP BETWEEN FORMAL CONTROL AND WORKPLACE DEVIANCE: A Proposed Framework

Abstract: Several studies in the field of management, organizational psychology, sociology and criminology have reported that workplace deviance is related to organization/work variables, such as organizational justice, job satisfaction, perceived organizational support, and job stress, among others. However, few studies have attempted to consider the influence of formal control and workplace deviance. Even if any, they have reported conflicting findings. Therefore, a moderating variable is suggested. This paper propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…31 A person's religious values can affect self-control and reduce deviant behavior. 32,33 A study found that religiosity positively correlates with risk-averse actions. In fact, in the case of some religions and religious people tend to avoid risky actions such as corruption.…”
Section: Religiositymentioning
confidence: 99%
See 1 more Smart Citation
“…31 A person's religious values can affect self-control and reduce deviant behavior. 32,33 A study found that religiosity positively correlates with risk-averse actions. In fact, in the case of some religions and religious people tend to avoid risky actions such as corruption.…”
Section: Religiositymentioning
confidence: 99%
“…65 Therefore, a religious background and knowledge instilled in an individual can help reduce their level of corruption because they can control themselves in facing normal situations and irregularities within the workplace. 32 Hence, religiosity can prevent individuals from committing fraud and corruption. 31 Therefore, based on previous studies, this study hypothesized that:…”
Section: E-government Religiosity and Corruptionmentioning
confidence: 99%
“… 33 A person’s religious values can affect self-control and reduce deviant behavior. 34 , 35 A study found that religiosity positively correlates with risk-averse actions. In fact, in the case of some religions and religious people tend to avoid risky actions such as corruption.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 67 Therefore, a religious background and knowledge instilled in an individual can help reduce their level of corruption because they can control themselves in facing normal situations and irregularities within the workplace. 34 Hence, religiosity can prevent individuals from committing fraud and corruption. 33 Therefore, based on previous studies, this study hypothesized that: H 2 : Religiosity has a moderating effect on the link between E-government and corruption …”
Section: Hypothesis Developmentmentioning
confidence: 99%